Powder of niobium-containing oxide, electrode therewith, and electricity storage device

The niobium-containing oxide powder with partial Ti substitution and surface treatment addresses the limitations of existing materials by maintaining high discharge capacity and rate characteristics, and reducing electrode thickness changes, enhancing battery performance in both liquid-based and all-solid-state lithium-ion batteries.

JP2025010141AActive Publication Date: 2025-01-20UBE CORPORATION
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024168551
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-20
Estimated Expiration
2043-06-29

AI Technical Summary

Technical Problem

Existing niobium-containing oxide powders used as negative electrode materials in lithium-ion batteries face issues with low energy density, high specific surface area leading to reduced initial efficiency, and poor charge/discharge rate characteristics, along with significant changes in electrode thickness during cycling, which affect the performance and capacity of all-solid-state batteries.

Method used

A niobium-containing oxide powder is developed with specific compositional and structural properties, including partial substitution of Ti with other elements, controlled particle size distribution, and surface treatment with Mo or Ce, enhancing conductivity and stability during charging and discharging.

Benefits of technology

The modified niobium-containing oxide powder maintains high initial discharge capacity and rate characteristics while minimizing electrode thickness changes, improving the performance of both liquid-based and all-solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010141000001
    Figure 2025010141000001
  • Figure 2025010141000002
    Figure 2025010141000002
  • Figure 2025010141000003
    Figure 2025010141000003
Patent Text Reader

Abstract

To provide niobium-containing oxide powder used as an electrode material of a nonaqueous electrolyte electricity storage device, excellent in rate characteristics while maintaining an initial discharge capacity, small in thickness change rate of an electrode accompanying charge and discharge, and excellent in the initial discharge capacity with a whole solid battery, and rate characteristics, an electrode therewith, and an electricity storage device.SOLUTION: Niobium-containing oxide powder satisfies the following formula (I) or (II): AaTi2-x(M10.5+vM20.5-v)xNb14O39±z (I) AaTi2-y(M10.67+wM30.33-w)yNb14O39±z (II) (wherein A is at least one element selected from Li and Na, M1 is at least one element selected from Nb, Ta, and V, M2 is at least one element selected from Al, Ga, Fe, and Cr, M3 is at least one element selected from the group consisting of Mg, Ca, Cu, and Zn, and 0≤a≤6, -0.05≤v≤0.05, -0.05≤w≤0.05, 0<x<2, 0<y<2, 0≤z≤1).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a niobium-containing oxide powder suitable as an electrode material for an electricity storage device, an electrode using the same, and an electricity storage device. [Background technology]

[0002] Electrical storage devices for electric vehicles require high energy density in order to improve fuel efficiency or power consumption, and lithium-ion batteries in particular are widely used as power sources for electric vehicles and power storage. Various materials have been researched as electrode materials for lithium-ion batteries, and although lithium titanate has excellent input / output characteristics, its energy density remains at 175mAh / g, and there are still challenges to be overcome in order to further increase its energy. Therefore, as an alternative candidate, there is a movement to use niobium-containing oxides, mainly niobium titanate, which has a high energy density of 380mAh / g, as negative electrode materials.

[0003] In addition, lithium-ion batteries currently on the market use electrolytes that contain flammable organic solvents, so they require the installation of safety devices to suppress temperature rises in the event of a short circuit and structures to prevent short circuits. Under these circumstances, all-solid-state secondary batteries that use inorganic solid electrolytes instead of organic electrolytes have attracted attention. Since the positive and negative electrodes and electrolytes of all-solid-state secondary batteries are all solid, there is a possibility that they can significantly improve the safety and reliability issues that are problems with batteries that use organic electrolytes. In addition, since safety devices can be simplified, high energy density can be achieved, so they are expected to be applied to electric vehicles, large storage batteries, etc.

[0004] Non-Patent Documents 1 and 2 describe porous Ti2Nb2N3N4N4N5N2 ... 14 O 39 and Ti2Nb produced by solid phase method. 14 O 39 When applied as an electrode material for an electricity storage device, Ti2Nb14 O 39 It has been reported that the rate characteristics are excellent in the case of TiNb2O7, TiNb 10 O 29 have been disclosed, which have been reported to have lower capacity loss with cycling than oxides that do not contain trivalent metals. [Prior art documents] [Non-patent literature]

[0005] [Non-Patent Document 1] Small 2017, 13, 1702903 [Non-Patent Document 2] Journal of Colloid and Interface Science 608 (2022) 90-102 [Patent documents]

[0006] [Patent Document 1] International Publication No. 2014 / 122376 Summary of the Invention [Problem to be solved by the invention]

[0007] However, the porous Ti2Nb 14 O 39 When used as a negative electrode material, it contains a large amount of conductive additive in order to ensure conductivity even inside the secondary particles. As a result, the ratio of active material in the negative electrode mixture becomes small, which causes a problem of a small energy density per negative electrode. In addition, since the specific surface area is very large, there is also a problem of a large drop in initial efficiency. Furthermore, when such porous particles are applied to an all-solid-state battery, the inside of the secondary particles cannot come into contact with the solid electrolyte, and therefore capacity cannot be obtained. In addition, Ti2Nb 14 O 39When the negative electrode was evaluated with a negative electrode having a high ratio of active material and a low ratio of conductive additive, there was an issue that the charge / discharge rate characteristics were reduced. 14 O 39 Although the battery characteristics were improved by controlling the particle size and specific surface area of ​​TiNb2O7 and Ti2Nb 10 O 29 Although batteries using TiNb2O7 and Ti2Nb have shown improvements in rate characteristics, they have a problem of a large decrease in battery capacity with cycling. 10 O 29 It was found that the change in electrode thickness during charging and discharging was large, resulting in a decrease in cycle life. The benefits of increasing battery capacity include an increase in energy density per unit weight or unit area (unit volume), which can lead to an extension of the driving range of electric vehicles and the creation of more space for storage batteries.

[0008] For the above reasons, the energy density, discharge rate characteristics, charge rate characteristics, and change in electrode thickness during charging and discharging of electricity storage devices using the negative electrode active materials of Non-Patent Document 1, Non-Patent Document 2, and Patent Document 1 are not fully satisfactory, and further improvements are necessary.

[0009] Therefore, an object of the present invention is to provide a niobium-containing oxide powder that can be used as an electrode material for a non-aqueous electrolyte electricity storage device, and that in a liquid lithium ion secondary battery, has excellent rate characteristics while maintaining an initial discharge capacity, has a small rate of change in electrode thickness due to charge and discharge, and also has excellent initial discharge capacity and rate characteristics in an all-solid-state battery, an electrode for an electricity storage device using the same, and an electricity storage device. [Means for solving the problem]

[0010] As a result of various investigations aimed at achieving the above object, the present inventors have found that Ti2Nb 14 O 39The inventors have found that by using, as an electrode material, a niobium-containing oxide powder in which part of Ti in a niobium-containing oxide such as those described above is substituted with a different element, it is possible to obtain an electricity storage device that is excellent in initial discharge capacity and rate characteristics and further has a small rate of change in electrode thickness due to charging and discharging, and have completed the present invention. Such an effect, in particular the effect of being able to reduce the change in electrode thickness due to charging and discharging, is not described or suggested at all in the above Non-Patent Documents 1 and 2 and Patent Document 1. That is, the present invention relates to the following matters.

[0011] (1) A niobium-containing oxide powder satisfying the following formula (I) or (II): A a Ti 2-x (M 1 0.5+v M 2 0.5-v ) x Nb 14 O 39±z (I) A a Ti 2-y (M 1 0.67+w M 3 0.33-w ) y Nb 14 O 39±z (II) (In the formula, A is at least one element selected from Li and Na, and M 1 is at least one element selected from Nb, Ta, and V; M 2 is at least one element selected from Al, Ga, Fe, and Cr; M 3 is at least one element selected from the group consisting of Mg, Ca, Cu, and Zn, and 0≦a≦6, −0.05≦v≦0.05, −0.05≦w≦0.05, 0 <x<2、0<y<2、0≦z≦1) (2) The niobium-containing oxide powder according to (1), characterized in that the D50 of primary particles corresponding to a volume cumulative 50% in a volume-based particle size distribution by a laser diffraction scattering method of the niobium-containing oxide powder is 0.25 μm or more and 4.5 μm or less. (3) The specific surface area of ​​the niobium-containing oxide powder is 2.3 m 2 / g or more 10m 2 The niobium-containing oxide powder according to (1) or (2), wherein the niobium content is 1 / g or less. (4) An electrode for a non-aqueous electrolyte electricity storage device, comprising the niobium-containing oxide powder according to any one of (1) to (3). (5) A negative electrode active material composition for a non-aqueous electrolyte storage device, comprising the niobium-containing oxide powder according to any one of (1) to (3) above and an inorganic solid electrolyte. (6) An electricity storage device comprising the electrode according to (4). (7) An all-solid-state secondary battery comprising a positive electrode layer, a negative electrode layer, and a solid electrolyte layer, the negative electrode layer being a layer containing the negative electrode active material composition according to (5). Effect of the Invention

[0012] According to the present invention, it is possible to provide a niobium-containing oxide powder which, in a liquid lithium ion secondary battery of a nonaqueous electrolyte electricity storage device, has excellent charge / discharge rate characteristics while maintaining an initial discharge capacity, and further has a small change in electrode thickness due to charge / discharge, and which also has excellent initial discharge capacity and rate characteristics in an all-solid-state battery, an electrode for an electricity storage device using the same, and an electricity storage device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] [Niobium-containing oxide powder of the present invention] The niobium-containing oxide powder of the present invention is a niobium-containing oxide powder that satisfies the following formula (I) or (II). A a Ti 2-x (M 1 0.5+v M 2 0.5-v ) x Nb 14 O 39±z (I) A a Ti 2-y (M 1 0.67+w M 3 0.33-w ) y Nb 14 O 39±z(II) (In the formula, A is at least one element selected from Li and Na, and M 1 is at least one element selected from Nb, Ta, and V; M 2 is at least one element selected from Al, Ga, Fe, and Cr; M 3 is at least one element selected from the group consisting of Mg, Ca, Cu, and Zn, and 0≦a≦6, −0.05≦v≦0.05, −0.05≦w≦0.05, 0 <x<2、0<y<2、0≦z≦1) The niobium-containing oxide powder of the present invention is preferably used for electrodes of non-aqueous electrolyte storage devices. That is, the niobium-containing oxide powder of the present invention is preferably used as a niobium-containing oxide powder for electrodes of non-aqueous electrolyte storage devices. The non-aqueous electrolyte may be any electrolyte other than an aqueous electrolyte, and is not particularly limited, but may include, for example, a non-aqueous electrolyte solution or a solid electrolyte.

[0014] <General formula A a Ti 2-x (M 1 0.5+v M 2 0.5-v ) x Nb 14 O 39±z and general formula A a Ti 2-y (M 1 0.67+w M 3 0.33-w ) y Nb 14 O 39±z Niobium-containing oxide powder represented by the formula: The niobium-containing oxide powder of the present invention is represented by the general formula A a Ti 2-x (M 1 0.5+v M 2 0.5-v ) x Nb 14 O 39±z Or general formula A a Ti 2-y (M 1 0.67+w M 30.33-w ) y Nb 14 O 39±z (wherein A is at least one element selected from Li and Na, and M 1 is at least one element selected from Nb, Ta, and V, and M 2 is at least one element selected from Al, Ga, Fe, and Cr, and M 3 is at least one element selected from the group consisting of Mg, Ca, Cu, and Zn, 0 ≦ a ≦ 6, -0.05 ≦ v ≦ 0.05, -0.05 ≦ w ≦ 0.05, 0 < x < 2, 0 < y < 2, 0 ≦ z ≦ 1). The niobium-containing oxide powder is contained. For the niobium-containing oxide, a titanium oxide phase (for example, rutile-type TiO2, TiO, etc.) derived from the synthesis raw material may be partially included.

[0015] The above A is not particularly limited as long as it is at least one element selected from Li and Na, but Li is preferable. The above M 1 is not particularly limited as long as it is at least one element selected from Nb, Ta, and V, but Nb is preferable.

[0016] The above M 2 is not particularly limited as long as it is at least one element selected from Al, Ga, Fe, and Cr, but Al, Fe, and Cr are preferable, Al and Fe are more preferable, and Al is even more preferable.

[0017] The above M 3 is not particularly limited as long as it is at least one element selected from the group consisting of Mg, Ca, Cu, and Zn, but Mg, Cu, and Zn are preferable, Cu and Zn are more preferable, and Cu is even more preferable.

[0018] General formula A a Ti 2-x (M 1 0.5+v M 2 0.5-v ) x Nb 14 O39±z and general formula A a Ti 2-y (M 1 0.67+w M 3 0.33-w ) y Nb 14 O 39±z wherein 0 ≦ a ≦ 6, preferably 0 ≦ a ≦ 2, more preferably 0 ≦ a ≦ 0.5, and even more preferably a = 0. Also, -0.05 ≦ v ≦ 0.05, preferably -0.01 ≦ v ≦ 0.01, more preferably v = 0. Also, -0.05 ≦ w ≦ 0.05, preferably -0.01 ≦ w ≦ 0.01, more preferably w = 0. Also, 0 < x < 2, preferably 0 < x ≦ 1.3, more preferably 0 < x ≦ 1, even more preferably 0 < x ≦ 0.9, and even more preferably 0 < x ≦ 0.5. Also, 0 < y < 2, preferably 0 < y ≦ 1.4, more preferably 0 < y ≦ 0.9, even more preferably 0 < y ≦ 0.6. Also, 0 ≦ z ≦ 1, preferably 0 ≦ z ≦ 0.5, more preferably 0 ≦ z ≦ 0.2, and even more preferably z = 0. Note that general formula A a Ti 2-y (M 1 0.67+w M 3 0.33-w ) y Nb 14 O 39±z wherein the ratio of M 1 to M 3 is M 1 :M 3 = 0.67 + w:0.33 - w, but M 1 :M 3 = 2 / 3 + w:1 / 3 - w may also be used. That is, in this case, when w = 0, M 1 :M 3 = 2 / 3:1 / 3 (i.e., A a Ti 2-y (M 1 2 / 3 M 3 1 / 3 ) y Nb 14 O 39±z ) is obtained.

[0019] <Content of at least one metal element selected from the group consisting of Mo and Ce> The niobium-containing oxide powder of the present invention may contain at least one metal element selected from the group consisting of Mo and Ce. Containing at least one metal element selected from the group consisting of Mo and Ce means that it is localized and present on the surface of the niobium-containing oxide particles constituting the powder. More specifically, it means that at least one metal element selected from the group consisting of Mo and Ce is localized and present in a larger amount in the surface region than in the internal region of the niobium-containing oxide particles. Also, in the inductively coupled plasma atomic emission spectrometry (ICP-AES) or X-ray fluorescence analysis (XRF) of the niobium oxide powder of the present invention, it means that at least one metal element selected from the group consisting of Mo and Ce is detected. The lower limit of the detection amount by inductively coupled plasma atomic emission spectrometry is usually 0.001% by mass. Mo and Ce may be contained in two kinds on the particle surface of the niobium-containing oxide powder. From the viewpoint of improving the initial discharge capacity and rate characteristics, it is preferable to contain Mo.

[0020] The content rate (% by mass) of at least one metal element selected from the group consisting of Mo and Ce in the niobium-containing oxide powder of the present invention determined by X-ray fluorescence analysis (XRF) may be 0.01 or more and 2.0 or less. If the content rate of at least one metal element selected from the group consisting of Mo and Ce is within this range, a secondary battery excellent in initial discharge capacity and rate characteristics can be obtained. It is preferably 0.01 or more and 1.7 or less, more preferably 0.015 or more and 1.5 or less, still more preferably 0.04 or more and 1.3 or less, even more preferably 0.07 or more and 1.25 or less, and particularly preferably 0.2 or more and 1.1 or less from the viewpoint of further improving the charge rate characteristics. However, when Mo and Ce are simultaneously contained on the particle surface of the niobium-containing oxide powder, the content rate (% by mass) is the total content rate of the two metal elements.

[0021] As an example, in the cross-sectional analysis of the niobium-containing oxide particles using a scanning transmission electron microscope, it is sufficient that at least one metal element selected from the group consisting of Mo and Ce is contained in a large amount in the so-called near-surface region from the surface of the niobium-containing oxide particles to a depth of about 20 nm measured by energy dispersive X-ray spectroscopy, and it is preferable that at least one metal element selected from the group consisting of Mo and Ce is detected at a depth position of 20 nm from the surface of the niobium-containing oxide particles, while Mo and Ce are not detected at a depth position of 100 nm from the surface, and in such a state, it can be determined that at least one metal element selected from the group consisting of Mo and Ce is localized on the surface of the niobium-containing oxide particles. That is, when measured by energy dispersive X-ray spectroscopy, it means that it is below the amount detected by the measurement, and the lower limit of the amount detected by the measurement by energy dispersive X-ray spectroscopy varies depending on the element and state to be measured, but is usually 0.5 atm%. Other surface analysis techniques include X-ray photoelectron spectroscopy (XPS) and Auger electron spectroscopy (AES). In the present invention, the form of the at least one metal element selected from the group consisting of Mo and Ce that is localized on the surface of the niobium-containing oxide particle is not particularly limited, and it is sufficient that at least one metal element selected from the group consisting of Mo element and Ce element is localized on the surface, and it may be in a metallic state or in the form of a metal compound such as a metal oxide.

[0022] <d50> D50 of the primary particles of the niobium-containing oxide powder of the present invention is an index of the volume median particle size. It means the particle size at which the cumulative volume frequency calculated from the volume fraction determined by laser diffraction / scattering particle size distribution measurement is 50% when calculated from the smallest particle size. The measurement method will be described in the examples below.

[0023] The niobium-containing oxide powder of the present invention may be a primary particle or a secondary particle formed by agglomeration of the primary particles. When the primary particles made of niobium-containing oxide particles contain secondary particles formed by agglomeration, a part of the secondary particles may not form secondary particles and may be in the form of the primary particles themselves.

[0024] When the niobium-containing oxide powder of the present invention is a secondary particle, the lower limit of the D50 of the secondary particle is preferably 5 μm or more, more preferably 7 μm or more, and even more preferably 9 μm or more, from the viewpoint of improving the electrode density. Furthermore, the upper limit of the D50 of the secondary particle is preferably 20 μm or less, more preferably 18 μm or less, and even more preferably 14 μm or less.

[0025] In the present invention, the primary particle D50 of the niobium-containing oxide powder is preferably 0.25 μm or more, more preferably 0.4 μm or more, and even more preferably 0.6 μm or more, from the viewpoint of improving the initial discharge capacity and rate characteristics in a liquid lithium ion secondary battery of a non-aqueous electrolyte storage device, and further the initial discharge capacity and rate characteristics in an all-solid-state battery. The upper limit of the primary particle D50 is preferably 4.5 μm or less, more preferably 4 μm or less, even more preferably 3 μm or less, even more preferably 2 μm or less, and particularly preferably 1.8 μm or less. The niobium-containing oxide powder may contain primary particles having a primary particle size of less than 0.4 μm, or may contain primary particles having a primary particle size of more than 4.5 μm.

[0026] <d90> In terms of the initial discharge capacity and rate characteristics of a liquid-type lithium-ion secondary battery of a nonaqueous electrolyte storage device, and the initial discharge capacity and rate characteristics of an all-solid-state battery, the lower limit of D90 of the primary particles of the niobium-containing oxide powder of the present invention is preferably 0.8 μm or more, more preferably 1.0 μm or more, and even more preferably 1.2 μm or more. The upper limit of D90 of the primary particles is preferably 20 μm or less, more preferably 15 μm or less, even more preferably 10 μm or less, even more preferably 5 μm or less, and particularly preferably 3 μm or less. The D90 of the primary particles of the niobium-containing oxide powder means the particle size at which the cumulative volume frequency calculated from the volume fraction obtained by laser diffraction / scattering particle size distribution measurement is 90% when calculated from the smallest particle size. The measurement method will be described in the examples described later.

[0027] <d10> In terms of the initial discharge capacity and rate characteristics of a liquid-based lithium-ion secondary battery of a non-aqueous electrolyte storage device, and the initial discharge capacity and rate characteristics of an all-solid-state battery, the D10 of the primary particles of the niobium-containing oxide powder of the present invention is preferably 0.05 μm or more, more preferably 0.1 μm or more, and even more preferably 0.2 μm or more. The upper limit of the D10 of the primary particles is preferably 0.9 μm or less, more preferably 0.8 μm or less, even more preferably 0.7 μm or less, and even more preferably 0.6 μm or less. The D10 of the primary particles of the niobium-containing oxide powder means a particle size at which the cumulative volume frequency calculated from the volume fraction obtained by laser diffraction / scattering particle size distribution measurement is 10% when calculated from the smallest particle size. The measurement method will be described in the examples described later.

[0028] <Specific surface area> The specific surface area of ​​the niobium-containing oxide powder of the present invention is the surface area per unit mass when nitrogen is used as an adsorption gas. The measuring method will be described in the examples below.

[0029] The niobium-containing oxide powder of the present invention has a specific surface area of ​​10 m 2 / g or less, 8.0m 2 / g or less is preferable, and 6.0m 2 / g or less is more preferable, and 4.0m 2 On the other hand, the lower limit of the specific surface area is 1.5 m 2 / g or more, 2.0m 2 / g or more is preferable, and 2.1m 2 / g or more is more preferable, and 2.4m 2 / g or more is more preferable, and 3.0m 2 Within the above range, a nonaqueous electrolyte electricity storage device having excellent initial discharge capacity and rate characteristics in a liquid lithium ion secondary battery, and an all-solid-state battery having excellent initial discharge capacity and rate characteristics can be obtained.

[0030] Ti2Nb 14 O 39 The reason why a remarkable effect was observed by using a niobium-containing oxide in which a part of Ti was replaced with a different element is not clear, but it is thought to be as follows. Generally, Ti2Nb 14 O 39 Negative electrode active materials such as niobium-containing oxide powders such as Ti2Nb2O3, TiNb3O4, TiNb4O5, TiNb5O6, TiNb6O7, TiNb7O8, TiNb8O9, TiNb9O10, TiNb11, TiNb12, TiNb13, TiNb14, TiNb15, TiNb16, TiNb17, TiNb18, TiNb20, TiNb30, TiNb40, TiNb50, TiNb6O11, TiNb12, TiNb13, TiNb20, TiNb30, TiNb40, TiNb50, TiNb6O11, TiNb15, TiNb16, TiNb17, TiNb20, TiNb30, TiNb40, TiNb50, TiNb6O11, TiNb12, TiNb13 ...30, TiNb40, TiNb50, TiNb6O11, TiNb6O12, TiNb7O13, TiNb8O14, TiNb9O15, TiNb15, TiNb16, TiNb17, TiNb18, TiNb19, TiNb19, TiNb19, TiNb20, TiNb21, TiNb30, TiNb30, TiNb40, TiNb50, TiNb6O11, TiNb12, TiNb13, TiNb20, TiNb30, TiNb30, TiNb40, TiNb50, TiNb6O1 14 O 39 It is believed that the unique crystal structure of Ti2Nb 14 O 39 and TiNb2O7 and Ti2Nb 10 O 29 It is believed that this resulted in battery characteristics that could not be achieved with conventional methods.

[0031] [Method of producing the niobium-containing oxide powder of the present invention] An example of the method for producing the niobium-containing oxide powder of the present invention will be described below, divided into a raw material preparation step and a firing step, but the method for producing the niobium-containing oxide powder of the present invention is not limited thereto.

[0032] <Raw material preparation process> First, the starting materials are mixed. As the starting materials, an oxide or salt containing at least one element selected from the group consisting of Ta, V, Al, Ga, Fe, Cr, Mg, Ca, Cu, and Zn, in addition to an oxide containing Ti and Nb, is used and mixed in a stoichiometric ratio to obtain the target composition of the present invention. The salt used is preferably a salt that has a relatively low melting point and decomposes to produce an oxide, such as a hydroxide salt, carbonate salt, or nitrate salt. In addition, in order to reduce the primary particle size, it is preferable to use a powder having an average primary particle size of 2 μm or less, preferably an average primary particle size of 0.5 μm or less, as the starting material.

[0033] The method for mixing the raw materials is not particularly limited, and either wet mixing or dry mixing may be used. For example, a Henschel mixer, an ultrasonic dispersing device, a homomixer, a mortar, a ball mill, a centrifugal ball mill, a planetary ball mill, a vibration ball mill, an attritor type high speed ball mill, a bead mill, a roll mill, etc. may be used.

[0034] <Firing process> Next, the mixture obtained above is fired. The firing is preferably performed in the temperature range of 500 to 1200°C, more preferably in the range of 700 to 1150°C, and even more preferably in the range of 900 to 1150°C. By performing the firing temperature at 1150°C or less, general-purpose equipment can be used. When the mixture is fired for a short period of time, it is preferable to prepare the mixed powder constituting the mixture before firing so that D95 in the particle size distribution curve measured by a laser diffraction / scattering type particle size distribution measuring device is 5 μm or less. Here, D95 refers to the particle size at which the cumulative volume frequency calculated by volume fraction is 95% when integrated from the smallest particle size.

[0035] The calcination method is not particularly limited as long as it can be performed under the above conditions. Examples of calcination methods that can be used include fixed bed calcination furnaces, roller hearth calcination furnaces, mesh belt calcination furnaces, fluidized bed calcination furnaces, and rotary kiln calcination furnaces. However, in the case of performing efficient calcination in a short time, roller hearth calcination furnaces, mesh belt calcination furnaces, and rotary kiln calcination furnaces are preferred. In particular, the rotary kiln calcination furnace is a particularly preferred calcination furnace for producing the niobium-containing oxide powder of the present invention, since it does not require a container to accommodate the mixture, it can be calcined while continuously feeding the mixture, the thermal history of the calcined material is uniform, and a homogeneous oxide can be obtained.

[0036] <Surface treatment process> The niobium-containing oxide obtained above may be subjected to a surface treatment. By having at least one metal element selected from the group consisting of Mo and Ce present locally on the surface of the particles constituting the niobium-containing oxide powder of the present invention, when the powder is applied as a negative electrode material of a battery, a dense negative electrode layer can be formed and excellent charge rate characteristics can be imparted. In the firing step, a compound containing at least one metal element selected from the group consisting of Mo and Ce (hereinafter, sometimes referred to as a treatment agent) can be added to produce the niobium-containing oxide powder of the present invention that has been surface-treated, but it is more preferable to produce the niobium-containing oxide powder of the present invention that has been surface-treated by the following surface treatment step or the like. In particular, by adopting the following surface treatment step, it is possible to appropriately and relatively simply make the surface of the niobium-containing oxide particles have at least one metal element selected from the group consisting of Mo and Ce present.

[0037] There is no particular limitation on the method of mixing the niobium-containing oxide powder as the base material with the compound containing at least one metal element selected from the group consisting of Mo and Ce, and either wet mixing or dry mixing can be used. However, it is preferable to uniformly disperse the compound containing at least one metal element selected from the group consisting of Mo and Ce on the surfaces of the particles constituting the niobium-containing oxide powder as the base material, and in this respect, wet mixing is preferred.

[0038] In the wet mixing, the treatment agent and the niobium-containing oxide powder of the substrate are put into a water or alcohol solvent and mixed in a slurry state. As the alcohol solvent, those with a boiling point of 100°C or less, such as methanol, ethanol, and isopropyl alcohol, are preferred because they are easy to remove. In addition, from an industrial perspective, water solvents are preferred because they are easy to recover and dispose of.

[0039] Compounds (treatment agents) containing at least one metal element selected from the group consisting of Mo and Ce are not particularly limited, and examples thereof include oxides, phosphoric oxides, hydroxides, sulfate compounds, nitrate compounds, fluorides, chlorides, organic compounds, and metal salt compounds such as ammonium salts and phosphates. Specifically, compounds of Mo include molybdenum oxide, molybdenum trioxide, molybdenum trioxide hydrate, molybdenum boride, molybdophosphoric acid, molybdenum disilicide, molybdenum chloride, molybdenum sulfide, molybdosilicic acid hydrate, sodium molybdenum oxide, molybdenum carbide, molybdenum acetate dimer, lithium molybdate, sodium molybdate, potassium molybdate, calcium molybdate, magnesium molybdate, manganese molybdate, and ammonium molybdate, and among these, molybdenum trioxide, molybdenum trioxide hydrate, molybdenum chloride, molybdenum sulfide, and lithium molybdate are preferred. Examples of Ce compounds include cerium oxide, cerium hydroxide, cerium fluoride, cerium sulfate, cerium nitrate, cerium carbonate, cerium acetate, cerium oxalate, cerium chloride, cerium boride, and cerium phosphate. Of these, cerium sulfate and its hydrates are preferred.

[0040] The amount of the compound containing at least one metal element selected from the group consisting of Mo and Ce may be any amount as long as the amount of the at least one metal element selected from the group consisting of Mo and Ce in the niobium-containing oxide falls within the range of the present invention, but it may be added at a rate of 0.03 mass% or more, preferably 0.05 mass% or more, relative to the niobium-containing oxide powder of the substrate. Also, it may be added at a rate of 12 mass% or less, preferably 10 mass% or less, more preferably 8 mass% or less, relative to the niobium-containing oxide powder of the substrate.

[0041] It is preferable to carry out a heat treatment after carrying out the surface treatment. The heat treatment temperature is a temperature at which the at least one metal element selected from the group consisting of Mo and Ce diffuses into at least the surface region of the niobium-containing oxide particles constituting the niobium-containing oxide powder of the base material, and is a temperature at which the specific surface area does not decrease significantly due to sintering of the niobium-containing oxide of the base material. The upper limit of the heat treatment temperature is preferably 700°C or less, more preferably 600°C or less. The lower limit of the heat treatment temperature is preferably 300°C or more, more preferably 400°C or more. The heat treatment time is preferably 0.1 hours to 8 hours, more preferably 0.5 hours to 5 hours. The temperature and time at which the at least one metal element selected from the group consisting of Mo and Ce diffuses into at least the surface region of the niobium-containing oxide powder of the base material differ in reactivity depending on the compound containing at least one metal element selected from the group consisting of Mo and Ce, so they should be appropriately set. In addition, the heating method in the heat treatment is not particularly limited. Examples of heat treatment furnaces that can be used include fixed bed furnaces, roller hearth furnaces, mesh belt furnaces, fluidized bed furnaces, and rotary kiln furnaces. The atmosphere during the heat treatment may be either an air atmosphere or an inert atmosphere such as a nitrogen atmosphere. In particular, when a metal salt compound is used for the surface treatment, an air atmosphere is preferred because anion species are easily removed from the particle surface.

[0042] It is preferable to perform a crushing process on the niobium-containing oxide powder obtained after the heat treatment as described above, if necessary, in order to set the specific surface area within the above range. The crushing process can be performed, for example, using a ball mill, and the conditions for the crushing process are not particularly limited as long as they are conditions that allow the specific surface area to be within the above range. In addition to the crushing process, classification may be performed.

[0043] The niobium-containing oxide powder of the present invention may be granulated and heat-treated to form a powder containing secondary particles formed by aggregation of primary particles. Any method for granulation may be used as long as secondary particles can be formed, but a spray dryer is preferred because it can process a large amount of the powder.

[0044] In order to reduce the amount of moisture contained in the niobium-containing oxide powder of the present invention, dew point control may be performed in the heat treatment process. If the heat-treated powder is exposed to the air as it is, moisture in the air will be adsorbed by the powder, so it is preferable to handle the powder in a dew point controlled environment during cooling in the heat treatment furnace and after the heat treatment. The heat-treated powder may be classified as necessary to make the particles within the desired maximum particle size range. When dew point control is performed in the heat treatment process, it is preferable to seal the niobium-containing oxide powder of the present invention in an aluminum laminate bag or the like and then place it in an environment outside of dew point control. Even under dew point control, if the heat-treated niobium-containing oxide powder is pulverized, moisture will be easily absorbed from the crushed surface, and the amount of moisture contained in the powder will increase, so it is preferable not to pulverize the powder after heat treatment. As for the heat treatment conditions, the temperature and holding time in a specific range greatly affect the secondary particle morphology and the surface treatment process. The heat treatment temperature is preferably 450°C or higher, and preferably less than 550°C. This is because if the heat treatment temperature exceeds 550°C, the specific surface area will be significantly reduced, and the battery performance, especially the rate characteristics, will be significantly reduced. Furthermore, the holding time is preferably one hour or longer, because if the holding time is short, not only will the amount of moisture in the powder increase, but it is also thought to affect the surface condition of the particles.

[0045] [Active material] The active material of the present invention contains the niobium-containing oxide powder of the present invention. It may contain one or more substances other than the niobium-containing oxide powder of the present invention. Examples of other substances include carbon materials (pyrolytic carbons, cokes, graphites (artificial graphite, natural graphite, etc.), organic polymer compound combustion bodies, carbon fibers), tin and tin compounds, silicon and silicon compounds, and metal oxides containing lithium. In particular, Li4Ti5O 12 Lithium titanate having the main component is exemplified.

[0046] [Electricity storage device] The electricity storage device of the present invention is a device that includes an electrode containing the active substance material of the present invention and stores and releases energy by utilizing the intercalation and deintercalation of lithium ions into such an electrode, and examples of such a device include a hybrid capacitor and a lithium battery.

[0047] [Hybrid capacitor] The hybrid capacitor is a device that uses an active material such as activated carbon, which forms a capacitance by physical adsorption similar to the electrode material of an electric double layer capacitor, an active material such as graphite, which forms a capacitance by physical adsorption and intercalation / deintercalation, or an active material such as a conductive polymer, which forms a capacitance by redox, in the positive electrode, and the active material of the present invention in the negative electrode. The active material of the present invention is usually used in the form of an electrode sheet of the hybrid capacitor.

[0048] [Lithium battery] The lithium battery of the present invention is a general term for lithium primary batteries and lithium secondary batteries. In this specification, the term lithium secondary battery is used as a concept including so-called lithium ion secondary batteries and all-solid-state lithium ion secondary batteries.

[0049] The lithium battery is composed of a positive electrode, a negative electrode, and a non-aqueous electrolyte in which an electrolyte salt is dissolved in a non-aqueous solvent, or a solid electrolyte, and the active material of the present invention can be used as an electrode material. The active material of the present invention is usually used in the form of an electrode sheet for the lithium battery. This active material may be used as either a positive electrode active material or a negative electrode active material, but the following description will be given of the case where it is used as a negative electrode active material.

[0050] <Negative electrode> The negative electrode has a negative electrode layer containing a negative electrode active material (the active material of the present invention), a conductive agent, and a binder on one or both sides of a negative electrode current collector. This negative electrode layer is usually in the form of an electrode sheet. In the case of a negative electrode current collector having pores such as a porous body, the negative electrode layer contains a negative electrode active material (the active material of the present invention), a conductive agent, and a binder in the pores.

[0051] The conductive agent for the negative electrode is not particularly limited as long as it is an electron conductive material that does not undergo chemical changes. For example, graphites such as natural graphite (e.g., flake graphite) and artificial graphite, carbon blacks such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, carbon nanotubes such as single-phase carbon nanotubes, multi-layer carbon nanotubes (graphite layers are multi-layered concentric cylinders) (non-fishbone-shaped), cup-laminated carbon nanotubes (fishbone-shaped), nodular carbon nanofibers (non-fishbone structure), and platelet-type carbon nanofibers (playing cards).

[0052] The amount of conductive agent added should be optimized because it varies depending on the specific surface area of ​​the active material and the type and combination of conductive agents. It is preferably 0.1% by mass to 10% by mass, more preferably 0.5% by mass to 5% by mass in the negative electrode layer. If it is less than 0.1% by mass, the conductivity of the negative electrode layer cannot be ensured, and if it exceeds 10% by mass, the active material ratio decreases, and the discharge capacity of the power storage device per unit mass and unit volume of the negative electrode layer becomes insufficient, so it is not suitable for increasing the capacity. The conductive agent may be added when the electrode is prepared, or may be coated on the active material itself. This is because the conductivity of the negative electrode layer can be further improved by coating with a conductive agent such as carbon fiber.

[0053] Examples of the binder for the negative electrode include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinylpyrrolidone (PVP), styrene-butadiene copolymer (SBR), acrylonitrile-butadiene copolymer (NBR), and carboxymethyl cellulose (CMC).

[0054] The amount of binder added should be optimized since it varies depending on the specific surface area of ​​the active material and the type and combination of the conductive agent, but is preferably 0.2% by mass to 15% by mass in the negative electrode layer. From the viewpoint of increasing the binding property and ensuring the strength of the negative electrode layer, it is preferably 0.5% by mass or more, more preferably 1% by mass or more, and even more preferably 2% by mass or more. From the viewpoint of preventing a decrease in the active material ratio and a decrease in the discharge capacity of the power storage device per unit mass and unit volume of the negative electrode layer, it is preferably 10% by mass or less, and more preferably 5% by mass or less.

[0055] Examples of the negative electrode current collector include aluminum, stainless steel, nickel, copper, titanium, baked carbon, and those having their surfaces coated with carbon, nickel, titanium, silver, etc. The surface of these materials may be oxidized, or the surface of the negative electrode current collector may be roughened by surface treatment.

[0056] The negative electrode can be produced by uniformly mixing the negative electrode active material (including the active material of the present invention), the conductive agent, and the binder in a solvent to prepare a paint, which is then applied to the negative electrode current collector, dried, and compressed. In the case of a negative electrode current collector having pores, such as a porous body, the paint is pressed into the pores of the current collector to fill the pores, or the current collector having pores is immersed in the paint to diffuse the pores, and then dried and compressed.

[0057] As a method for uniformly mixing the negative electrode active material (the active material of the present invention), the conductive agent, and the binder in a solvent to prepare a paint, for example, a kneader of the type in which a stirring rod revolves while rotating in a kneading vessel such as a planetary mixer, a twin-screw extrusion type kneader, a planetary stirring defoamer, a bead mill, a high-speed rotating type mixer, a powder suction continuous dissolution and dispersion device, etc. Also, as a manufacturing process, the process may be divided according to the solid content concentration, and these devices may be used separately.

[0058] In order to mix the negative electrode active material (the active material of the present invention), the conductive agent and the binder uniformly in the solvent, the mixing should be optimized because it depends on the specific surface area of ​​the active material, the type of conductive agent, the type of binder and the combination of these. However, when using a kneader in which the stirring rod revolves while rotating in a kneading container such as a planetary mixer, a twin-screw extrusion type kneader, a planetary stirring degassing device, etc., it is preferable to divide the steps according to the solid content concentration in the manufacturing process, knead the mixture in a state where the solid content concentration is high, and then gradually reduce the solid content concentration to adjust the viscosity of the paint. The high solid content concentration is preferably 60% by mass to 90% by mass, more preferably 60% by mass to 80% by mass. If it is 60% by mass or more, it is preferable because shear force can be obtained, if it is 90% by mass or less, it is preferable because the load on the device is reduced, and if it is 80% by mass or less, it is more preferable.

[0059] The mixing procedure is not particularly limited, but examples thereof include a method of simultaneously mixing the negative electrode active material, the conductive agent, and the binder in a solvent, a method of previously mixing the conductive agent and the binder in a solvent and then adding and mixing the negative electrode active material, a method of previously preparing a negative electrode active material slurry, a conductive agent slurry, and a binder solution, and then mixing each of them, etc. Among these, in order to disperse them uniformly, a method of previously mixing the conductive agent and the binder in a solvent and then adding and mixing the negative electrode active material, and a method of previously preparing a negative electrode active material slurry, a conductive agent slurry, and a binder solution, and then mixing each of them are preferred.

[0060] As the solvent, an organic solvent can be used. Examples of the organic solvent include aprotic organic solvents such as 1-methyl-2-pyrrolidone, dimethylacetamide, and dimethylformamide, which may be used alone or in combination of two or more kinds, and preferably 1-methyl-2-pyrrolidone.

[0061] When an organic solvent is used as the solvent, it is preferable to dissolve the binder in the organic solvent before use.

[0062] <Positive electrode> The positive electrode has a positive electrode layer containing a positive electrode active material, a conductive agent, and a binder on one or both sides of a positive electrode current collector.

[0063] As the positive electrode active material, a material capable of absorbing and releasing lithium is used. For example, the active material may be a composite metal oxide containing lithium and containing cobalt, manganese, or nickel, or a lithium-containing olivine-type phosphate. These positive electrode active materials may be used alone or in combination of two or more. Examples of such composite metal oxides include LiCoO2, LiMn2O4, LiNiO2, LiCo 1-x Ni x O2(0.01 <x<1)、LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, LiNi 1 / 2 Mn 3 / 2 O4, etc., and these lithium composite oxides may be partially substituted with other elements, and a portion of the cobalt, manganese, and nickel may be partially substituted with at least one element such as B, Nb, Sn, Mg, Fe, Ti, Al, Zr, Cr, V, Ga, Zn, Cu, Bi, Mo, and La, a portion of the O may be substituted with S or F, or a compound containing these other elements may be coated. Examples of lithium-containing olivine-type phosphates include LiFePO4, LiCoPO4, LiNiPO4, LiMnPO4, LiFe 1-x MxPO4 (M is at least one selected from Co, Ni, Mn, Cu, Zn, and Cd, and x is 0≦x≦0.5).

[0064] The conductive agent and binder for the positive electrode may be the same as those for the negative electrode. The positive electrode current collector may be, for example, aluminum, stainless steel, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, or silver. The surface of these materials may be oxidized, or the positive electrode current collector surface may be roughened by surface treatment.

[0065] <Nonaqueous electrolyte> The non-aqueous electrolyte is a non-aqueous solvent having an electrolyte salt dissolved therein. There are no particular limitations on the type of non-aqueous electrolyte, and various types can be used.

[0066] The electrolyte salt used is one that dissolves in a non-aqueous electrolyte, and examples of the electrolyte salt include inorganic lithium salts such as LiPF6, LiBF4, LiPO2F2, LiN(SO2F)2, and LiClO4; lithium salts containing a chain-like fluorinated alkyl group such as LiN(SO2CF3)2, LiN(SO2C2F5)2, LiCF3SO3, LiC(SO2CF3)3, LiPF4(CF3)2, LiPF3(C2F5)3, LiPF3(CF3)3, LiPF3(iso-C3F7)3, and LiPF5(iso-C3F7); lithium salts containing a cyclic fluorinated alkylene chain such as (CF2)2(SO2)2NLi and (CF2)3(SO2)2NLi; and lithium salts having an oxalate complex as the anion, such as lithium bis[oxalate-O,O']borate and lithium difluoro[oxalate-O,O']borate. Among these, particularly preferred electrolyte salts are LiPF6, LiBF4, LiPO2F2, and LiN(SO2F)2, and the most preferred electrolyte salt is LiPF6. These electrolyte salts can be used alone or in combination of two or more.

[0067] The concentration of all of these electrolyte salts dissolved in the nonaqueous solvent is usually preferably 0.3 M or more, more preferably 0.5 M or more, and even more preferably 0.7 M or more. The upper limit is preferably 2.5 M or less, more preferably 2.0 M or less, and even more preferably 1.5 M or less.

[0068] On the other hand, the non-aqueous solvent may be a cyclic carbonate, a chain carbonate, a chain ester, an ether, an amide, a phosphoric acid ester, a sulfone, a lactone, a nitrile, an S=O bond-containing compound, etc., and preferably contains a cyclic carbonate. The term "chain ester" is used as a concept including a chain carbonate and a chain carboxylate ester.

[0069] Examples of the cyclic carbonate include one or more selected from ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 4-fluoro-1,3-dioxolan-2-one (FEC), trans- or cis-4,5-difluoro-1,3-dioxolan-2-one (hereinafter, both are collectively referred to as "DFEC"), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), and 4-ethynyl-1,3-dioxolan-2-one (EEC). From the viewpoints of improving the charge rate characteristics of the electricity storage device and suppressing the amount of gas generation during high temperature operation, one or more selected from the group consisting of ethylene carbonate, propylene carbonate, 1,2-butylene carbonate, 2,3-butylene carbonate, 4-fluoro-1,3-dioxolan-2-one, and 4-ethynyl-1,3-dioxolan-2-one (EEC) are more preferred, and one or more cyclic carbonates having an alkylene chain selected from propylene carbonate, 1,2-butylene carbonate, and 2,3-butylene carbonate are even more preferred.

[0070] In particular, it is preferable to use a non-aqueous electrolyte solution having a total electrolyte salt concentration of 0.5 M to 2.0 M, containing at least LiPF6 as the electrolyte salt, and further containing at least one lithium salt selected from LiBF4, LiPO2F2, and LiN(SO2F)2 at 0.001 M to 1 M. When the proportion of lithium salts other than LiPF6 in the non-aqueous solvent is 0.001 M or more, the effect of improving the charge rate characteristics of the electricity storage device and suppressing the amount of gas generation during high-temperature operation is easily exhibited, and when it is 1.0 M or less, there is little concern that the effect of improving the charge rate characteristics of the electricity storage device and suppressing the amount of gas generation during high-temperature operation will decrease, which is preferable.

[0071] In addition, the non-aqueous solvent is preferably used in a mixed state in order to achieve appropriate physical properties. Examples of the combination include a combination of a cyclic carbonate and a chain carbonate, a combination of a cyclic carbonate, a chain carbonate and a lactone, a combination of a cyclic carbonate, a chain carbonate and an ether, a combination of a cyclic carbonate, a chain carbonate and a chain ester, a combination of a cyclic carbonate, a chain carbonate and a nitrile, and a combination of a cyclic carbonate, a chain carbonate and a compound containing an S=O bond.

[0072] Suitable examples of the chain ester include one or more asymmetric chain carbonates selected from methyl ethyl carbonate (MEC), methyl propyl carbonate (MPC), methyl isopropyl carbonate (MIPC), methyl butyl carbonate, and ethyl propyl carbonate; one or more symmetric chain carbonates selected from dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, and dibutyl carbonate; pivalic acid esters such as methyl pivalate, ethyl pivalate, and propyl pivalate; and one or more chain carboxylate esters selected from methyl propionate, ethyl propionate, propyl propionate, methyl acetate, and ethyl acetate (EA).

[0073] <The structure of a lithium battery> The structure of the lithium battery of the present invention is not particularly limited, and examples include a coin battery having a positive electrode, a negative electrode, and a single-layer or multi-layer separator, and further, a cylindrical battery or a square battery having a positive electrode, a negative electrode, and a roll-shaped separator.

[0074] The separator is an insulating thin film having a large ion permeability and a certain mechanical strength. Examples of the separator include polyethylene, polypropylene, cellulose paper, glass fiber paper, polyethylene terephthalate, and polyimide microporous membranes, and multi-layer membranes made by combining two or more of them can also be used. The surface of these separators can also be coated with resins such as PVDF, silicone resins, and rubber-based resins, or particles of metal oxides such as aluminum oxide, silicon dioxide, and magnesium oxide.

[0075] <Negative electrode active material composition> The negative electrode active material composition of the present invention is a negative electrode active material composition containing the niobium-containing oxide powder of the present invention and an inorganic solid electrolyte having conductivity of metal ions belonging to Group 1 of the periodic table. The content of the inorganic solid electrolyte is not particularly limited, but may be 1% by mass or more in the active material composition, preferably 5% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more. The higher the content of the inorganic solid electrolyte, the easier it is to obtain contact between the niobium-containing oxide powder and the solid electrolyte, which is preferable. In addition, if the content of the inorganic solid electrolyte is too high, the battery capacity of the all-solid-state secondary battery becomes small, so the content may be 70% by mass or less, preferably 60% by mass or less. In general, in order to increase the battery capacity of the all-solid-state secondary battery, it is preferable that the content of the inorganic solid electrolyte is small, but if the content is small, it becomes difficult to obtain contact between the niobium-containing oxide powder and the solid electrolyte. By using the niobium-containing oxide powder used in the negative electrode active material composition of the present invention, a satisfactory contact between the niobium-containing oxide powder and the solid electrolyte can be obtained even when the content of the inorganic solid electrolyte is small. The niobium-containing oxide powder and inorganic solid electrolyte of the present invention may contain one or more substances other than the inorganic solid electrolyte. Examples of the other substances include carbon materials (pyrolytic carbons, cokes, graphites (artificial graphite, natural graphite, etc.), organic polymer compound combustion bodies, carbon fibers), tin and tin compounds, silicon and silicon compounds, and metal oxides containing lithium. In particular, Li4Ti5O 12 Lithium titanate having the main component is exemplified.

[0076] <Periodic table> The periodic table in this specification refers to a long-form periodic table of elements based on the provisions of IUPAC (International Union of Pure and Applied Chemistry).

[0077] <Solid electrolyte> A solid electrolyte is a solid electrolyte that can move ions inside. In particular, inorganic solid electrolytes are solid in a stationary state, and therefore are not usually dissociated or liberated into cations and anions. Inorganic solid electrolytes are not particularly limited as long as they have the conductivity of metal ions belonging to Group 1 of the periodic table, and generally have almost no electronic conductivity. Representative examples of inorganic solid electrolytes include (A) sulfide inorganic solid electrolytes, (B) oxide inorganic solid electrolytes, and (C) chloride inorganic solid electrolytes. In particular, sulfide inorganic solid electrolytes are preferably used because they have high ionic conductivity and can form a dense molded body with few grain boundaries by simply applying pressure at room temperature. The periodic table referred to here refers to the long-period type periodic table.

[0078] The sulfide inorganic solid electrolyte may be a non-crystalline glass, a crystallized glass, or a crystalline material. Specific examples of the sulfide inorganic solid electrolyte include, but are not limited to, the following combinations. Li2S-P2S5, Li2S-P2S5-Al2S3, Li2S-GeS2, Li2S-Ga2S3, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S -GeS2-Sb2S5, Li2S-GeS2-Al2S3, Li2S-SiS2, Li2S-Al2S3, Li2S-SiS2-Al2S3, Li2S-SiS2-P2S5, Li 10 GeP2S 12 .

[0079] Among the above combinations, LPS glass and LPS glass ceramics produced by combining Li2S-P2S5 are preferred. In addition, other sulfide inorganic solid electrolytes such as argerodite-type solid electrolytes such as Li6PS5Cl and Li6PS5Br are also suitable.

[0080] The oxide inorganic solid electrolyte contains oxygen atoms and preferably has metal ions belonging to Group 1 of the periodic table, has ionic conductivity and has electron insulation.

[0081] Examples of the oxide inorganic solid electrolyte include, for example, Li having a LISICON (Lithium super ionic conductor) type crystal structure, 3.5 Zn 0.25 GeO4, La having a perovskite type crystal structure, 0.55 Li 0.35 TiO3, LiTi2P3O having a NASICON (Natrium super ionic conductor) type crystal structure, 12 Li7La3Zr2O having a garnet type crystal structure, 12 (LLZ), lithium phosphate (Li3PO4), LiPON in which a part of the oxygen of lithium phosphate is substituted with nitrogen, Li3BO3-Li2SO4, Li2O-B2O3-P2O5, Li2O-SiO2, and Li6BaLa2Ta2O, 12 etc. are preferably mentioned.

[0082] Examples of the chloride inorganic solid electrolyte include Li3ScCl6, LiAlCl4, Ln, 1-X A X OCl 1-X (wherein Ln represents any rare earth element, A represents an alkaline earth metal, and X is 0 < X < 1), etc. are preferably mentioned.

[0083] The volume average particle diameter of the inorganic solid electrolyte is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.1 μm or more. The upper limit is preferably 100 μm or less, more preferably 50 μm or less.

Examples

[0084] Next, the present invention will be described in more detail with reference to examples and comparative examples. However, the present invention is not limited to the following examples and includes various combinations that can be easily inferred from the gist of the invention.

[0085] (Lithium-ion secondary battery) [Example 1-1] <Raw material preparation process> Nb2O5 (average particle size 0.2μm), anatase type TiO2 (specific surface area 10m 2 niobium-containing oxide (TiO2 / g) and Al2O3 were weighed out to a molar ratio of 78.5:21.2:0.3 and mixed. This mixed powder was calcined at 1,050°C for 12 hours. Powder X-ray diffraction measurements were performed on the calcined powder sample obtained at a sampling interval of 0.01° and a scan speed of 2° / min. No peaks derived from the starting materials were observed, confirming that the reaction had progressed completely. From the results of crystal structure analysis of the synthesized sample and X-ray fluorescence analysis (XRF) using an X-ray fluorescence spectrometer (manufactured by SII Technology Inc., product name "SPS5100"), it was confirmed that the synthesized sample was the target niobium-containing oxide (Ti 1.9 Nb 14.05 Al 0.05 O 39 ) was confirmed.

[0086] <Crushing process> Zirconia beads having a diameter of 2.0 mm were added to the obtained fired powder sample, and the mixture was crushed in a ball mill to produce the niobium-containing oxide powder according to Example 1-1, in which the particle size distribution of the primary particles was adjusted.

[0087] [Examples 1-2 to 1-12] The niobium-containing oxide powders according to Examples 1-2 to 1-12 were produced in the same manner as in Example 1-1, except that the raw materials and mixing ratios were changed in the raw material preparation step so as to obtain the composition formulas shown in Tables 1 and 2.

[0088] [Comparative Example 1-1] Nb2O5 and anatase-type TiO2 were weighed and mixed so that the molar ratio was 7:2. Niobium-containing oxide powder according to Comparative Example 1-1 was produced by only subjecting this mixed powder to a firing treatment at 1100 °C for 12 hours without performing a crushing treatment step as in Non-Patent Document 1.

[0089] [Reference Example 1-1] Niobium-containing oxide powder according to Reference Example 1-1 was produced in the same manner as in Example 1-1 except that the molar ratio of Nb2O5 and anatase-type TiO2 was changed to 7:2.

[0090] [Measurement of Powder Physical Properties] Various physical properties of the niobium-containing oxide powders of each example, comparative example, and reference example were measured as follows.

[0091] [Measurement of Specific Surface Area] The specific surface area (m 2 / g) of the niobium-containing oxide powders of each example, each comparative example, and each reference example was measured using a fully automatic BET specific surface area measuring device (manufactured by Mountech Co., Ltd., trade name "Macsorb HM model-1208"), and nitrogen gas was used as the adsorption gas. 0.5 g of the measurement sample powder was weighed, placed in a φ12 standard cell (HM1201-031), degassed under vacuum at 100 °C for 0.5 hour, and then measured by the BET single-point method.

[0092] [Calculation of D50: Dry Laser Diffraction Scattering Method] The D50 of the primary particles of the niobium-containing oxide powders of each example, each comparative example, and each reference example was calculated from the particle size distribution curve measured using a laser diffraction / scattering type particle size distribution measuring machine (manufactured by Nikkiso Co., Ltd., Microtrac MT3300EXII). 50 mg of the sample was put into a container containing 50 ml of ion-exchanged water as the measurement solvent, and the measurement solvent was added until the transmittance of the slurry was within an appropriate range (the range indicated by the green bar of the device) to perform particle size distribution measurement. The D50 of the primary particles of the powder was calculated from the obtained particle size distribution curve.

[0093] [Evaluation of Battery Characteristics] The niobium-containing oxide powders of each of the Examples, Comparative Examples, and Reference Examples were used to fabricate coin-type batteries, and their battery characteristics were evaluated. The evaluation results are shown in Table 1.

[0094] <Preparation of negative electrode sheet> The negative electrode sheet was prepared as follows in a room controlled at a room temperature of 25°C and a dew point of -20°C or less. The niobium-containing oxide powder of each Example and Comparative Example was taken out of the aluminum laminated bag in a room controlled at a temperature of 25°C and a dew point of -20°C or less. The niobium-containing oxide powder of each Example and Comparative Example taken out was mixed in a ratio of 85 mass% as an active material, 10 mass% as acetylene black as a conductive agent, and 5 mass% as polyvinylidene fluoride as a binder to prepare a paint. The obtained paint was applied to an aluminum foil and dried to prepare a negative electrode single-sided sheet to be used in a coin battery described later.

[0095] <Preparation of electrolyte> The electrolyte used in the battery for characteristic evaluation was prepared as follows: In an argon glove box controlled at a temperature of 25°C and a dew point of -70°C or less, a non-aqueous solvent of ethylene carbonate (EC): dimethyl carbonate (DMC) = 1:2 (volume ratio) was prepared, and LiPF6 was dissolved in it as an electrolyte salt to a concentration of 1M to prepare the electrolyte for the coin battery described below.

[0096] <Preparation of coin battery> The negative electrode sheet prepared by the above method was punched into a circle with a diameter of 14 mm and a thickness of 2 t / cm 2 The electrode was pressed at a pressure of 1000 MPa and then vacuum dried at 120° C. for 5 hours to prepare an electrode for evaluation. The electrode for evaluation and metallic lithium (formed into a circle with a thickness of 0.5 mm and a diameter of 16 mm) were placed opposite each other via glass filters (one each of ADVANTEC GA-100 and Whatman GF / C), and the nonaqueous electrolyte prepared by the method described above in <Preparation of electrolyte> was added and sealed to prepare a 2032-type coin battery.

[0097] <Initial battery characteristics: initial discharge capacity, initial efficiency> The coin-type battery prepared by the method described in the above <Preparation of Coin Battery> was placed in a thermostatic chamber at 25°C and charged at 0.2 mA / cm in the direction in which Li was absorbed in the evaluation electrode. 2 The battery was charged to 1 V at a current density of 0.05 mA / cm at 1 V. 2 After constant current and constant voltage charging, the battery was charged to a current density of 0.2 mA / cm 2 A constant current discharge was performed at a current density of 0.01 to 3 V. The initial discharge capacity (mAh / g) was calculated by dividing the obtained discharge capacity (mAh) by the mass of the niobium-containing oxide, and the initial efficiency (%) was calculated by dividing the discharge capacity (mAh) by the charge capacity (mAh).

[0098] <10C rate charge / discharge rate measurement> The battery was charged to 1V at a current equivalent to 10C of the initial discharge capacity, and then constant-current constant-voltage charging was performed at 1V until the charging current reached a current density of 0.05C. The battery was then discharged to 3V at a current of 10C. The 10C rate charge rate (%) was calculated by dividing the capacity obtained by the 10C constant-current charging by the initial discharge capacity, and the 10C rate discharge rate (%) was calculated by dividing the capacity obtained by the 10C constant-current discharging by the initial discharge capacity. The results are shown in Tables 1 and 2. If the 10C rate characteristic of the niobium-containing oxide is high, it is expected that the discharge rate characteristic of the battery storage device will be improved when it is used as an electrode material for the battery storage device. The C in 1C represents the current value when charging and discharging. For example, 1C refers to the current value at which the theoretical capacity can be fully discharged (or fully charged) in 1 / 1 hour, and 0.1C refers to the current value at which the theoretical capacity can be fully discharged (or fully charged) in 1 / 0.1 hour.

[0099] [Table 1]

[0100] [Table 2]

[0101] <Evaluation Results> It was found that the electrodes using the niobium-containing oxide powders of Examples 1-1 to 1-12 had better 10C charge rate and 10C discharge rate and were superior in rate characteristics to the electrodes using the niobium-containing oxide powders of Comparative Example 1-1 and Reference Example 1-1 in which a portion of Ti was not replaced with a different element.

[0102] <Measurement of electrode thickness change rate due to charging and discharging> The coin-type battery prepared by the method described in the above <Preparation of Coin Battery> was placed in a thermostatic chamber at 25°C and charged at 0.2 mA / cm in the direction in which Li was absorbed in the evaluation electrode. 2 The battery was charged to 0.8 V at a current density of 0.05 mA / cm at 0.8 V. 2 After constant current and constant voltage charging, the battery was charged to a current density of 0.2 mA / cm 2 The battery was discharged to 2 V at a current density of 0.2 mA / cm. 2 The battery was charged to 0.8 V at a current density of 0.05 mA / cm at 0.8 V. 2 After constant-current constant-voltage charging was performed until the current density reached 0.8 V, the coin battery was disassembled, the negative electrode sheet in the charged state was taken out, and its thickness was measured. The thickness of the negative electrode sheet after charging to 0.8 V was divided by the thickness of the negative electrode sheet before the coin battery was made to calculate the rate of change in electrode thickness due to charging and discharging.

[0103] <Evaluation Results> The electrode thickness change rate during charging and discharging using the niobium-containing oxide powder of Example 1-1 was 10.5%, and the electrode thickness change rate during charging and discharging using the niobium-containing oxide powder of Example 1-2 was 10.5%. 10 O 29 The thickness change rate of the electrode using the niobium-containing oxide powder of the present invention due to charging was 13.4%, and it was found that the electrode using the niobium-containing oxide powder of the present invention had a smaller thickness change due to charging and discharging than the electrode using the niobium-containing oxide powder described in Patent Document 1. This effect is not described at all in Non-Patent Documents 1, 2, and Patent Document 1. In addition, from the results of Example 1-1, it is considered that the effect of suppressing the electrode thickness change rate due to charging and discharging of the electrode can be similarly obtained in Examples 1-2 to 1-12 other than Example 1-1.

[0104] (All-solid-state secondary battery) [Example 2-1] In a glove box under an argon atmosphere, the niobium-containing oxide of Example 1-3, the sulfide solid electrolyte Li6PS5Cl powder (volume average particle size: 6 μm obtained using a laser diffraction / scattering type particle size distribution analyzer), and the conductive agent were weighed out so that the mass ratio of niobium-containing oxide: Li6PS5Cl: conductive agent = 60: 40: 6 was obtained, and the mixture was stirred and mixed using an agate mortar and a planetary ball mill to obtain the negative electrode active material composition of Example 2-1. The obtained negative electrode active material composition was pressed (360 MPa) at room temperature for 10 minutes to produce a pellet (molded body) with a diameter of 10 mm and a thickness of about 0.7 mm. A pellet-shaped electrode containing this negative electrode active material composition, a pellet-shaped solid electrolyte layer (LPS glass with a molar ratio of Li2S: P2S5 = 75: 25) as a separator layer, and a lithium indium alloy foil as a counter electrode were laminated in this order, and the laminate was sandwiched between stainless steel current collectors to produce an all-solid-state secondary battery, and the battery characteristics were evaluated. The evaluation results are shown in Table 3.

[0105] [Example 2-2] The procedure was the same as in Example 2-1 except that the niobium-containing oxide in Example 1-9 was used instead, and an all-solid-state secondary battery according to Example 2-2 was fabricated and its battery characteristics were evaluated. The evaluation results are shown in Table 3.

[0106] [Example 2-3] Ion-exchanged water was added to the niobium-containing oxide of Example 1-3 so that the solid content of the slurry was 30 mass%, and lithium molybdate (Li2MоO4) was added as a treatment agent at 0.8 mass% per 100 g of the niobium-containing oxide to prepare a mixed slurry. This mixed slurry was mixed for 3 hours with a paint shaker, dried at a temperature of 100°C, and then heat-treated for 1 hour at 500°C in a muffle furnace to produce a niobium-containing oxide surface-treated with lithium molybdate according to Example 2-3. Then, the same procedure as in Example 2-1 was carried out except that the niobium-containing oxide surface-treated with the obtained lithium molybdate was used, and an all-solid-state secondary battery according to Example 2-3 was produced and its battery characteristics were evaluated. The evaluation results are shown in Table 3.

[0107] [Example 2-4] Ion exchange water was added to the niobium-containing oxide of Example 1-9 so that the solid content of the slurry was 30 mass%, and lithium molybdate (Li2MоO4) was added as a treatment agent at 0.8 mass% per 100 g of the niobium-containing oxide to prepare a mixed slurry. This mixed slurry was mixed for 3 hours with a paint shaker, dried at a temperature of 100°C, and then heat-treated for 1 hour at 500°C in a muffle furnace to produce the niobium-containing oxide surface-treated with lithium molybdate according to Example 2-4. Then, the same procedure as in Example 2-1 was carried out except that the niobium-containing oxide surface-treated with the obtained lithium molybdate was used, and an all-solid-state secondary battery according to Example 2-4 was produced and its battery characteristics were evaluated. The evaluation results are shown in Table 3.

[0108] [Reference example 2-1] Except for using the niobium-containing oxide of Reference Example 1-1, the negative electrode active material composition of Reference Example 2-1 was obtained in the same manner as in Example 2-1, and then an all-solid-state secondary battery was produced and the battery characteristics were evaluated. The evaluation results are shown in Table 2.

[0109] [Comparative Example 2-1] Except for using the niobium-containing oxide of Comparative Example 1-1, the negative electrode active material composition of Comparative Example 2-1 was obtained in the same manner as in Example 2-1, and then an all-solid-state secondary battery was produced and the battery characteristics were evaluated. The evaluation results are shown in Table 2.

[0110] <Measurement of 1C rate characteristics> In a thermostatic chamber at 25°C, the all-solid-state secondary battery prepared by the above-mentioned method was charged to 0.5V with a current equivalent to 0.05C of the theoretical capacity of the niobium-containing oxide, with the direction of Li absorption in the evaluation electrode being the charging direction, and further constant current constant voltage charging was performed in which charging was performed at 0.5V until the charging current became a current equivalent to 0.01C, and the charging capacity (mAh) was divided by the mass of the niobium-containing oxide to obtain the initial charging capacity (mAh / g). Then, constant current discharging was performed to 2V with a current equivalent to 0.05C. The discharge capacity (mAh) was divided by the mass of the niobium-containing oxide to obtain the initial discharging capacity (mAh / g). Next, charging was performed to 0.5V with a current equivalent to 1C of the theoretical capacity of the niobium-containing oxide, and the 1C charging capacity was obtained. The 1C charging rate (%) was calculated by dividing the 0.4C charging capacity by the initial charging capacity. Then, the battery was discharged to 2V at a current equivalent to 1C of the theoretical capacity of the niobium-containing oxide, and the 1C discharge capacity was calculated. The 1C discharge capacity was divided by the initial discharge capacity to calculate the 1C discharge rate (%). The evaluation results are shown in Table 3.

[0111] [Table 3]

[0112] <Evaluation Results> It was found that the electrode using the niobium-containing oxide powder of the present invention in the all-solid-state battery also has a better initial discharge capacity and 1C rate characteristic than the electrode using the niobium-containing oxide powder of Reference Example 2-1 and Comparative Example 2-1 in which a part of Ti is not replaced with a different element. It was also found that the 1C charge / discharge rate characteristic was further improved in Examples 2-3 and 2-4 in which the surface was treated with lithium molybdate. It can be said that the niobium-containing oxides surface-treated with lithium molybdate according to Examples 2-3 and 2-4 have Mo localized on the surface due to their manufacturing method.

[0113] In Examples 1-1 to 1-12 and 2-1 to 2-4, which used the niobium-containing oxide powder of the present invention in which part of Ti was replaced with a different element, the effect of improving the rate characteristics was observed regardless of the type of electricity storage device.

[0114] The niobium-containing oxide powder obtained by the present invention is useful as an electrode active material for lithium-ion batteries because it can improve the rate characteristics while maintaining the initial discharge capacity. An electricity storage device using this niobium-containing oxide powder as an electrode active material is useful as a secondary battery for driving or backing up various devices such as automobiles and electronic devices, and for storing power at night in homes and offices. By providing electrode materials for lithium-ion batteries, such as non-aqueous electrolyte secondary batteries, to society, it is possible to contribute to the achievement of Goal 12 (ensure sustainable consumption and production patterns), Goal 3 (ensure healthy lives and promote well-being for all at all ages), Goal 7 (ensure access to affordable, reliable, sustainable and modern energy for all), and Goal 11 (make cities and human settlements inclusive, safe, resilient and sustainable) out of the 17 goals of the Sustainable Development Goals (SDGs) established by the United Nations.

Claims

1. A niobium-containing oxide powder satisfying the following formula (I) or (II): A a Ti 2-x (M 1 0.5+v M 2 0.5-v ) x Nb 14 O 39±z (I) A a Till 2-y (M) 1 0.67+w M 3 0.33-w ) y N﹂ 14 Oh 39±z (II) (In the formula, A is at least one element selected from Li and Na, and M 1 is at least one element selected from Nb, Ta, and V; M 2 is at least one element selected from Al, Ga, Fe, and Cr; M 3 is at least one element selected from the group consisting of Mg, Ca, Cu, and Zn, and 0≦a≦6, −0.05≦v≦0.05, −0.05≦w≦0.05, 0<x<2, 0<y<2, 0≦z≦1)

2. The niobium-containing oxide powder according to claim 1, characterized in that the D50 of primary particles corresponding to a volume cumulative of 50% in a volume-based particle size distribution by a laser diffraction scattering method of the niobium-containing oxide powder is 0.25 μm or more and 4.5 μm or less.

3. The niobium-containing oxide powder has a specific surface area of ​​2.3 m 2 / g or more 10m 2 The niobium-containing oxide powder according to claim 1 or claim 2, wherein the niobium content is 1 / g or less.

4. An electrode for an electricity storage device, comprising the niobium-containing oxide powder according to claim 1 or 2 as an active material.

5. A negative electrode active material composition for a non-aqueous electrolyte storage device, comprising the niobium-containing oxide powder according to claim 1 or 2 and an inorganic solid electrolyte.

6. A non-aqueous electrolyte electricity storage device comprising the electrode according to claim 4.

7. 6. An all-solid-state secondary battery comprising a positive electrode layer, a negative electrode layer, and a solid electrolyte layer, the negative electrode layer being a layer containing the negative electrode active material composition according to claim 5.

Citation Information

Patent Citations

  • Active material and production method therefor, nonaqueous electrolyte battery and battery pack

    JP2014103110A

  • Complex and manufacturing method thereof, active substance material for nonaqueous electrolyte battery, and nonaqueous electrolyte battery

    JP2016033851A

  • Mixed oxides of titanium and niobium containing trivalent metals

    JP2016510304A

  • Active material, electrode, secondary battery, battery pack and vehicle

    JP2019169343A

  • Niobium-containing oxide powder, electrodes using same, and power storage devices

    JP7597280B1